Rising China, anxious Asia? A Bayesian New Keynesian view - Wong, Chin Yoong; Eng, Yoke Kee; Habibullah, Muzafar Shah (Elsevier, 2014)
Should Asia feel anxious about China's expansion? We look for the answer through the Bayesian estimation of a two-country New Keynesian model of production fragmentation covering ten Asian economies, including China. The estimates show that vis-à-vis China, the developed Asia has a more fragmented production structure with higher domestic value-added embodied in intermediates traded with China whereas the developing Asian production chains are equally if not less fragmented with more foreign value-added. We also find that China's expansion made possible by favorable demand and price shocks benefits all Asian neighbors. Expansion driven by total factor productivity improvement, however, lifts the aggregate value-added in the developing Asia but not in the developed Asia, unless the shocks symmetrically originate in both China and the developed Asia. Fixing the regional currencies irrevocably to the U.S. dollar amplifies the effect of China's productivity improvements, although it is nearly irrelevant for responses to other types of shocks. We conclude that production fragmentation and symmetry in shock are the keys to the answers of this question.